Uafgørlighedsdidaktik i litteraturundervisningen - Johansen, Martin Blok (Nordlit, 2022)
Building on two situations from practice, the potential of undecidability - when it appears in schools’ literature teaching - is analyzed and discussed. This is done with a focus on undecidability in the field between the text, the students and the teacher. For this purpose, we set up a didactic model in three stages, which are: The ontology of undecidability; the typology of undecidability; and the mode of undecidability. In other words, what is undecidability? How can it be measured? And how does it play out? The purpose is to approach an actual didactic model of undecidability, where the point is that if the potential of undecidability is to be redeemed, all classroom actants must be on board; the text must contain undecidability, the teacher must dare to use it, and students should be receptive to it.
Keywords: undecidability; teaching literature; didactic; frictionality; Derrida